2020
DOI: 10.1049/iet-smt.2020.0277
|View full text |Cite
|
Sign up to set email alerts
|

Flow field distribution around insulator and contamination uneven characteristic of insulator

Abstract: The accumulation of insulator surface contamination is closely related to the distribution of flow field around the insulator. In order to study the unevenness of the insulator surface contamination, a three-unit lxy-160 insulator is selected. Based on the principle of fluid mechanics, the fluid movement state on the insulator surface is determined by the calculation of Reynolds number and boundary layer, then the flow field distribution around the insulator is obtained. On this basis, the artificial contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Qiao et al [4] simulated the pollution accumulation process of insulators by CFD software Ansys 15.0 and studied the pollution distribution of insulators with different shapes. Huang et al [5] explored the law of pollution accumulation on the surface of insulators by combining fluid dynamics calculation and experimentation. The results showed that when the wind speed was 3-7 m/s, the boundary layer separation existed for pollution particles within a 1-60 µm particle size, while the increase in wind speed and particle size of pollution would aggravate the nonuniformity of pollution accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Qiao et al [4] simulated the pollution accumulation process of insulators by CFD software Ansys 15.0 and studied the pollution distribution of insulators with different shapes. Huang et al [5] explored the law of pollution accumulation on the surface of insulators by combining fluid dynamics calculation and experimentation. The results showed that when the wind speed was 3-7 m/s, the boundary layer separation existed for pollution particles within a 1-60 µm particle size, while the increase in wind speed and particle size of pollution would aggravate the nonuniformity of pollution accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Li Te et al [25] studied the difference in the contamination characteristics between the composite rod insulator and the standard disc suspension insulator, and found that the contamination difference between the upper and lower surfaces of composite insulator was smaller than that of standard suspension insulators. Huang Yanchen et al [26] investigated the relationship between the contamination accumulation on the insulator surface and the distribution of the flow field around the insulator. In their work, when the wind speed was 3∼7 m/s, there was obvious separation of the boundary layer, and the contamination accumulation on the insulator surface was closely related to the distribution of the flow field around the insulator.…”
Section: Introductionmentioning
confidence: 99%